Public Perceptions of the Police, PCSPs and the Northern Ireland Policing Board : Report Based on the Northern Ireland Policing Board Module of the April 2016 Omnibus Survey.: Report Based on the Northern Ireland Policing Board Module of the April 2016 Omnibus Survey. (2016) - Northern Ireland Policing Board,; Northern Ireland Statistics & Research Agency,
No abstract available